(untitled) (CAHIERS MAGELLANES-NS, 2024)
The advent of social media has revolutionized the landscape of communication, offering unprecedented platforms for free expression. However, the intersection of freedom of speech and social media is fraught with complexity, as it involves balancing individual rights with community standards and platform policies. This abstract examines the evolving nature of free speech within social media contexts, analyzing key issues such as content moderation, censorship, and the impact of algorithms on public discourse. It explores how different social media platforms navigate these challenges and the implications for democratic engagement and societal norms. The discussion also considers legal frameworks and the role of government regulation in shaping the boundaries of acceptable speech online.